A atividade de trabalho no CAPS - Centro de Atenção Psicossocial: pois é José ... - Enio Rodrigues da Silva (2010)
This dissertation has the purpose understanding the psychiatrist work task at the CAPS - one of the devices of the Brazilian Psychiatrist Reform. The research was developed in two CAPS III of Belo Horizonte city, one CAPS III and II of Betim city/MG. We considered the theorical-methodological assumptions of the work psychology,based on the aspects of the Clinical work, inspired on the Ergonomic and Psychossocial Analyse of the work, as well as, in a more relevant way, the Ergology. We were supported in the concepts of prescribed and real work, and of the consequent lags to understand what psychiatrists do when they work at CAPS. We did an observation participant on the real work at CAPS, in order to unveiling the objective and subjective aspects of the operation of services and the work relationships. Then, we did in-depth interviews with psychiatrists workers and former workers psychologies, social assistants, nurses, occupational therapists, nursing assistants, beyond the pacients, in order to enlarge our researches on the psychiatrists team work. Empirically, the results obtained were large and pointed, in a singular way, to a confirmation of the distancing dichotomous between the prescribed-real, drawing a parallel between the concrete conditions and contradictions, work materials and the ideological political aspects. One study of the case will exemplify the situation that we present. As to CAPS, these were found in an aggregation process of working in itself, but also of reflection of work practices. In general, we found a bad feeling at the real work, translated by the fragility at the researches identity as works, at the precauriones of the clinical work process, in the psychic suffering/illness, in the work abandonment, especially the psychiatrists ones. At other instance, to ressingularizar and reframe the work requirement prescribed, the workers presented us strategies to deal with the working environment variability/infidelity. The subject of recognition at/ for work has also showed central in our research.